Non-enzymatic detection of glucose levels in human blood plasma by a graphene oxide-modified organic transistor sensor. Issue 17 (6th February 2023) - Fan, Haonan; Sasaki, Yui; Zhou, Qi; Tang, Wei; Nishina, Yuta; Minami, Tsuyoshi
Abstract : An organic transistor-based sensor functionalized with graphene oxide and a phenylboronic acid derivative shows an accurate detectability for glucose in human blood plasma by the minimization of physical protein adsorption on the detection electrode. Abstract : We herein report an organic transistor functionalized with a phenylboronic acid derivative and graphene oxide for the quantification of plasma glucose levels, which has been achieved by the minimization of interferent effects derived from physical protein adsorption on the detection electrode.